2021
DOI: 10.2478/acph-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antihyperglycemic activities of Scorzonera cinerea radical leaves in streptozocin-induced diabetic rats

Abstract: Scorzonera species are used for treating various diseases. They are consumed raw, especially in the spring, and have nutritious and dietetic values. This study evaluated the antidiabetic and antioxidant effects of ethanolic extracts of Scorzonera cinerea (Sc) radical leaves in diabetes mellitus. Five random groups of Wistar rats (n = 8) were created – control, diabetic, acarbose, Sc-Dried, and Sc-Frozen. Phenolic profiles of extracts were determined by HPLC. Free radical scavenging capacity was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…These mechanisms may be through inhibition of digestive enzymes and/or by acting like insulin-mimetic to reduce postprandial blood glucose (Temiz & Temur, 2019). Besides they might have antidiabetic effects such as reducing glucose absorption in the small intestine, stimulation of insulin secretion from islets, improving insulin sensibility, and increasing the uptake and bioavailability of glucose to the cells (Temiz and Temur, 2019;Temiz, 2021;Yang et al, 2015;Zhang et al, 2020). Backgrounds of these mechanisms have complex pathways in the cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms may be through inhibition of digestive enzymes and/or by acting like insulin-mimetic to reduce postprandial blood glucose (Temiz & Temur, 2019). Besides they might have antidiabetic effects such as reducing glucose absorption in the small intestine, stimulation of insulin secretion from islets, improving insulin sensibility, and increasing the uptake and bioavailability of glucose to the cells (Temiz and Temur, 2019;Temiz, 2021;Yang et al, 2015;Zhang et al, 2020). Backgrounds of these mechanisms have complex pathways in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, medicinal and wild edible plants have gained attention as they offer both an important source of food and natural remedies for various ailments (Milella et al, 2014). They also have nutritive and dietetic value, largely owing to the presence of complex carbohydrates, mineral salts, vitamins, and polyphenolic compounds (Sekeroglu et al, 2006;Temiz, 2021). Turkey is one of the countries that have rich flora in terms of medicinal, aromatic, and wild edible plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is equipped with hepatoprotective [ 21 ], gastroprotective [ 66 ], wound healing (epithelization or cell regeneration) [ 15 ], free radical scavenging, and antioxidative [ 21 ] features. Oxidative stress has been tied to the genesis of DM and its consequences [ 67 ]. Ultimately, the probable way by which G. lotoides brings about its antidiabetic effect may be by ameliorating insulin resistance and insufficiency through increasing pancreatic β-cell regeneration and attenuating β-cell slaying caused by chronic hyperglycaemia induced oxidant burden.…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-known fact that Scorzonera species are beneficial in many medical indications such as, common cold (such as mucolytic, diuretic and antipyretic), wound healing and against acute hepatotoxicity, arteriosclerosis, kidney diseases, hypertension, diabetes mellitus, rheumatism, pain (7,12,22,23). Studies related to Turkish folk medicine have mentioned that many of the Scorzonera species have antidiabetic properties (7,13) and a single recent study has been reported S. cinerea radical leaves have an antidiabetic effect by inhibiting α-amylase and α-glucosidase and increasing the insulin level in diabetic rats (24). Although all that background a study that examines the antidiabetic properties, with an up-to-date method, of many Scorzonera species was not found.…”
Section: Discussionmentioning
confidence: 99%
“…From the chemical point of view, the Scorzonera species have been subjected to intensive studies which have led to the isolation of several types of compounds. Previously, a number of compounds such as dihydroisocoumarines, bibenzyl derivatives, flavonoids, lignans, stilbene derivatives, quinic and caffeic acid derivatives, sesquiterpene, sesquiterpene lactones and triterpenes have been isolated from the Scorzonera species and many of the isolated compounds have been identified as new structures(8)(9)(10)12,(22)(23)(24)32,33). In current study none of the investigated Scorzonera species aerial parts except S. cana var.…”
mentioning
confidence: 80%